DIE ONGETROUDE VOLWASSE TSWANA-VROU SE PERSEPSIES VAN DIE HUWELIK - Erasmus, A; Ryke, EH (Social Work/Maatskaplike Werk, 2004)
The objective of this article is to explore and describe the adult unmarried Tswana woman’s perceptions of marriage in order to contribute to the development of indigenous knowledge as a basis for culture congruent marriage preparation services. For these purposes a qualitative, exploratory research study has been undertaken. Thirty-two Tswana women, who met all the set criteria, were included in the study by means of purposive sampling. An in-depth exploration of the perceptions of unmarried mature Tswana women was undertaken by utilising the semi-structured method of interviewing. Relevant data were analysed by means of descriptive analysis as described by Tesch. A variety of factors that influence the adult unmarried Tswana woman’s perceptions of marriage, such as the traditional and changing role and status of the married woman, the high divorce rate, the bogadi- and stay at in-laws-custom, and the Tswana woman’s expectation of a spouse, have been identified. In this article the findings of this study is presented and discussed, and recommendation regarding culture congruent marriage preparation services made.